Integrated policy analysis to identify transformation paths to more sustainable legume-based food and feed value-chains in Europe. Issue 6 (3rd July 2021) - Balázs, Bálint; Kelemen, Eszter; Centofanti, Tiziana; Vasconcelos, Marta W.; Iannetta, Pietro P.M.
ABSTRACT: The food- and feed-value systems in the European Union are not protein self-sufficient. Despite their potential to improve the well-being of arable cropping systems, sufficient production of high-protein legume grains in Europe has not been achieved due to multiple barriers. The reasons are multiple and span economic, agronomic, research, and extension services, as well as aspects of culture and traditional dietary habits. Given the well-documented advantages of legume-supported production systems and diets, that include ecosystem and health provisions, acknowledging and promoting legumes as cornerstone species for more sustainable agri-food systems is a necessary and logical step. This paper provides an integrated analysis of case studies and current policies that shape the production and consumption of legumes in Europe. This study identified three key pathways, which can be integrated into sustainable farming systems to support current and future food security challenges via the use of legumes and legume-based products. At each pathway, we identified several enablers that support the sustainability transformation of legume production and consumption in Europe.